PP97 Design and develop a self-emulsifying system prototype for topical application of Caribbean Colombian algae extracts with potential antimicrobial activity against acne-related microorganisms. - Rodriguez Martinez, Ingrid Andrea; Aragón Novoa , Diana Marcela; Castellanos Hernandez, Leonardo (Revista Productos Naturales, 2025)
The exploration of topical acne treatments used Dictyota extracts collected in Providencia, Colombian Caribbean. These extracts showed antimicrobial activity against Staphylococcus epidermidis and Cutibacterium acnes, linked to diterpenes and fatty acids that disrupt bacterial membranes. Using matrices and pseudoternary diagrams, a self-emulsifying system was designed, optimizing critical variables such as droplet size (